Sociocultural Intelligence And Prison Systems. The Fight Against Organised Crime Continues Beyond The Dismantling Of Organisations - Pascual, Daniel Sansó-Rubert (Advances in Social Sciences Research Journal, 2017)
Traditionally the fight against organised crime, as well as keeping any type of offensive measure outside of the prison environment, has been characterised by the absence of a minimum reflection about the strategies used, accumulating a number of significant strategic errors in the confrontation against the organised crime phenomenon. To the extent that, in recent decades, organised crime has taken the initiative. Having identified this reality and from a criminological perspective and that of the application of criminal intelligence capabilities, the prison system is configured as a fruitful field of research, useful to obtain sociocultural inputs (sociocultural criminal intelligence) which provide not only a better understanding of the organised criminal phenomenon, but also their leaders. This knowledge is based on criminological theories and allows for the development of focused deterrence and selective action strategies, not only against organisations as a whole or their activities and markets but also against their leaders, seeking thereby, the ultimate neutralisation of the phenomenon. Keywords: organised crime, criminal intelligence, sociocultural intelligence, prison systems, criminal subculture